Tumor cell-induced macrophage senescence plays a pivotal role in tumor initiation followed by stable growth in immunocompetent condition - Haruka Wada; Ryo Otsuka; Wilfred T V Germeraad; Tomoki Murata; Toru Kondo; Ken-ichiro Seino (Journal for ImmunoTherapy of Cancer, 2023)
Background The cancer stem cell theory proposes that tumor formation in vivo is driven only by specific tumor-initiating cells having stemness; however, clinical trials conducted to test drugs that target the tumor stemness provided unsatisfactory results thus far. Recent studies showed clear involvement of immunity in tumors; however, the requirements of tumor-initiation followed by stable growth in immunocompetent individuals remain largely unknown.Methods To clarify this, we used two similarly induced glioblastoma lines, 8B and 9G. They were both established by overexpression of an oncogenic H-RasL61 in p53-deficient neural stem cells. In immunocompromised animals in an orthotopic transplantation model using 1000 cells, both show tumor-forming potential. On the other hand, although in immunocompetent animals, 8B shows similar tumor-forming potential but that of 9G’s are very poor. This suggests that 8B cells are tumor-initiating cells in immunocompetent animals. Therefore, we hypothesized that the differences in the interaction properties of 8B and 9G with immune cells could be used to identify the factors responsible for its tumor forming potential in immunocompetent animals and performed analysis.Results Different from 9G, 8B cells induced senescence-like state of macrophages around tumors. We investigated the senescence-inducing factor of macrophages by 8B cells and found that it was interleukin 6. Such senescence-like macrophages produced Arginase-1, an immunosuppressive molecule known to contribute to T-cell hyporesponsiveness. The senescence-like macrophages highly expressed CD38, a nicotinamide adenine dinucleotide (NAD) glycohydrolase associated with NAD shortage in senescent cells. The addition of nicotinamide mononucleotide (NMN), an NAD precursor, in vitro inhibited to the induction of macrophage senescence-like phenotype and inhibited Arginase-1 expression resulting in retaining T-cell function. Moreover, exogenous in vivo administration of NMN after tumor inoculation inhibited tumor-initiation followed by stable growth in the immunocompetent mouse tumor model.Conclusions We identified one of the requirements for tumor-initiating cells in immunocompetent animals. In addition, we have shown that tumor growth can be inhibited by externally administered NMN against macrophage senescence-like state that occurs in the very early stages of tumor-initiating cell development. This therapy targeting the immunosuppressive environment formed by macrophage senescence-like state is expected to be a novel promising cancer therapeutic strategy.